2005
DOI: 10.1002/cncr.21338
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of histology and 1p/19q status in anaplastic oligodendroglial tumors

Abstract: BACKGROUND.It has been reported previously that the combined loss of chromosomal arms 1p and 19q is a significant predictor of outcome for patients with anaplastic oligodendroglial (AO) tumors and that such chromosomal loss correlates with classic histology in AO. The authors sought to determine whether histology was an equivalent or superior predictor of outcome compared with 1p/19q status in 131 patients with AO tumors. METHODS.The status of 1p and 19q was determined using real-time, quantitative polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 25 publications
7
73
0
3
Order By: Relevance
“…20,[30][31][32][33][34][35] With respect to the prognostic significance of genetic alterations, previous reports have mostly focussed on 1p/19q deletions, which were found to be significantly associated with longer survival of patients with oligodendroglial tumors. 10,12,[14][15][16][17]36 In line with these data, we found that combined 1p and 19q losses were associated with a better prognosis in our patients (increase in median patient survival of around 70 months, i.e. 5.8 years).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…20,[30][31][32][33][34][35] With respect to the prognostic significance of genetic alterations, previous reports have mostly focussed on 1p/19q deletions, which were found to be significantly associated with longer survival of patients with oligodendroglial tumors. 10,12,[14][15][16][17]36 In line with these data, we found that combined 1p and 19q losses were associated with a better prognosis in our patients (increase in median patient survival of around 70 months, i.e. 5.8 years).…”
Section: Discussionsupporting
confidence: 90%
“…6,9 Several of the genetic aberrations in oligodendroglial tumors have been associated with patient outcome. Most importantly, a number of retrospective [10][11][12][13][14][15] as well as recent prospective studies 16,17 have identified 1p/19q deletion as a powerful molecular marker of prolonged survival. Relatively few studies have addressed the prognostic role of other genomic alterations in oligodendroglial tumors.…”
mentioning
confidence: 99%
“…However, the outcome of patients with non-1p/19q codeleted tumors but with typical histological appearance was reported to be equally favorable in a large prospective U.S. trial [17]. Another study reported loss of 1p and 19q to be related, in particular, to outcome in patients with tumors with classic histologic features [27].…”
Section: Histomorphology and 1p/19q Codeletionmentioning
confidence: 99%
“…The 1p/19q codeletion is present in 61%-89% of AOD cases, but in only 13%-20% of patients with AOA [6,27]. Of note, McDonald et al [27] confirmed the close association between CFO and 1p/19q codeletion, with a higher likelihood of 1p and 19q loss if more pathologists judged the tumor to be CFO.…”
Section: Histomorphology and 1p/19q Codeletionmentioning
confidence: 99%
See 1 more Smart Citation